Effect of sweetener containing Stevia on the development of dental caries in enamel and dentin under a microcosm biofilm model - Nascimento, Caren Augustinho do (2021)
This study compared the effect of a commercial and pure sweetener containing Stevia to that of aspartame (commercial and pure), sucrose (common sugar), xylitol (a natural sweetener known to be anti-cariogenic) on the development of dental caries in a microcosm biofilm model formed over enamel and dentin. For this, 228 bovine enamel and 228 samples of bovine root dentin samples (4 mm x 4 mm) were prepared. In 24-well plates, each enamel or dentin sample was exposed to 1.5 mL of inoculum (human saliva-glycerol + McBain saliva, 1:50), for 8 h. After the initial 8 h, the inoculum was removed, the samples were washed with PBS (5 s), received 1.5 mL of fresh medium (McBain artificial saliva) for 16 h, completing the initial 24 h. From the 2nd to the 5th day of biofilm cultivation, the samples were exposed daily to McBain saliva supplemented with 0.2% of the respective sweeteners /sugar: Stevia, aspartame (both in pure or commercial form, Finn brand), xylitol, sucrose and control saliva (McBain) without supplementation (n = 3/plate, biological quadruplicate). The cultivation was carried out at 5% CO2 and 37ºC. The production of lactic acid (g/L) and colony-forming units (CFU) for total microorganisms, total lactobacilli, total streptococci and Streptococcus mutans/ S. sobrinus (log10 CFU/mL) were quantified in the biofilm. The degree of dental demineralization was analyzed using transverse microradiography-TMR. The data were compared statistically (Kruskal-Wallis / Dunn, p < 0.05). In the lactate analysis, the sweeteners pure stevia, pure aspartame, xylitol and control did not differ, reducing by 92% the production of this acid. The groups stevia finn, aspartame finn and sucrose showed higher production of lactic acid, being similar to each other (0.47 ± 0.14, 0.43 ± 0.10, 0.44 ± 0.13 g/L for enamel; 0.69 ± 0.19, 0.65 ± 0.11, 0.67 ± 0.24 g/L for dentin, respectively, p < 0.0001). Regarding the CFU counting for total lactobacilli and S. mutans/S. sobrinus, xylitol and control groups did not show colony growth on enamel. The species grew under exposure to stevia finn, aspartame finn and sucrose in enamel and dentin (5.69 ± 0.44, 5.69 ± 0.82, 5.75 ± 0.60 log10 CFU total lactobacilli/mL; 7.57 ± 0.37, 7.61 ± 0.64, 7.49 ± 0.41 log10 CFU S. mutans /mL; 0.00 ± 3.98, 5.30 ± 5.30, 5.30 ± 0.15 log10 CFU total lactobacilli/mL; 7.83 ± 0.36, 7.87 ± 0.18; 7.78 ± 0.31 log10 CFU S. mutans/mL for enamel and dentin, respectively). Enamel and dentin demineralization was significantly reduced for the xylitol, control, pure stevia and pure aspartame groups (approximately 85% and 83% reduction, respectively) compared to stevia finn, aspartame finn and sucrose which, in turn, did not differ from each other (Z: 3084.67 ± 834.26, 3174.67 ± 603.10, 2913.67 ± 646.69 vol%.m for enamel and 3945.67 ± 689.69, 3626.79 ± 617.26, 3543.33 ± 432.50 vol%.m for dentin). In conclusion, commercial sweeteners based on stevia and aspartame (Finn brand) proved to be as cariogenic as sucrose in this experimental model, which is due to the other components of these sweeteners, since the pure forms were not cariogenic.